BRANDING STRATEGY FOR MSME CULINARY PRODUCTS - A. A Gede Ajusta,; Wawan Ridwan,; Nanang Lidwan,; Eni Reptiningsih, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The culinary Micro, Small, and Medium Enterprises (MSMEs) sector is a strategic component of Indonesia’s economy, contributing significantly to employment creation and community income. However, in an increasingly competitive market, many MSMEs struggle to build a strong and sustainable brand image. This study aims to analyze branding strategies employed by culinary MSMEs and evaluate their effectiveness in enhancing business competitiveness. This research adopts a qualitative approach using a case study method involving five culinary MSMEs in urban areas. Data were collected through in-depth interviews, participatory observation, and visual documentation. Thematic analysis and SWOT framework were used to identify the strengths, weaknesses, opportunities, and threats of the branding strategies implemented. The findings show that common branding strategies include the use of visual identity (logos and packaging), brand storytelling, and the use of social media platforms such as Instagram and TikTok. MSMEs that implemented branding consistently reported increased brand awareness, customer loyalty, and sales volume. Major challenges faced include limited knowledge of branding, lack of time, and insufficient human resources. Effective branding has proven to improve MSME competitiveness, even with limited budgets. This study recommends branding training programs, digital mentoring, and collaborations between MSMEs and creative communities. Simple but consistent branding can be the key to maintaining business sustainability and expanding market reach for culinary MSMEs.